The "one airway, one disease" concept in light of Th2 inflammation. Issue 4 (25th October 2018) - Giovannini-Chami, Lisa; Paquet, Agnès; Sanfiorenzo, Céline; Pons, Nicolas; Cazareth, Julie; Magnone, Virginie; Lebrigand, Kévin; Chevalier, Benoit; Vallauri, Ambre; Julia, Valérie; Marquette, Charles-Hugo; Marcet, Brice; et al.
In line with the pathophysiological continuum described between nose and bronchus in allergic respiratory diseases, we assessed whether nasal epithelium could mirror the Type 2 T-helper cell (Th2) status of bronchial epithelium. Nasal and bronchial cells were collected by brushing from healthy controls (C, n=13), patients with allergic rhinitis and asthma (AR, n=12), and patients with isolated allergic rhinitis (R, n=14). Cellular composition was assessed by flow cytometry, gene expression was analysed by RNA sequencing and Th2, Type 17 T-helper cell (Th17) and interferon (IFN) signatures were derived from the literature. Infiltration by polymorphonuclear neutrophils (PMN) in the nose excluded 30% of the initial cohort. All bronchial samples from the AR group were Th2-high. The gene expression profile of nasal samples from the AR group correctly predicted the paired bronchial sample Th2 status in 71% of cases. Nevertheless, nasal cells did not appear to be a reliable surrogate for the Th2 response, in particular due to a more robust influence of the IFN response in 14 out of 26 nasal samples. The Th2 scores in the nose and bronchi correlated with mast cell count (both p<0.001) and number of sensitisations (p=0.006 and 0.002), while the Th17 scores correlated with PMN count (p=0.006 and 0.003). The large variability in nasal cell composition and type of inflammation restricts its use as a surrogate for assessing bronchial Th2 inflammation in AR patients. Nasal epithelial cells are not good surrogates for bronchial epithelial cells in the evaluation of Th2 inflammation http://ow.ly/if5u30ltyx5